Core concepts in athletic training and therapy - Hillman, Susan Kay , 1952- (Athletic training education series, 2012)
Suitable for first year students on sport physiotherapy, coaching and related health care courses, this text contains material that provides an introduction to the profession, the evaluation and implementation of sport health care and on to more advanced aspects of administration and management